Comparison between Vermicompost and Conventional Aerobic Compost Produced from Municipal Organic Solid Waste Used in Amaranthus viridis Production - Islam, MS; Hasan, M; Rahman, MM; Uddin, MN; Kabir, MH (Journal of Environmental Science and Natural Resources, 2017)
The study was conducted to determine the performance of vermicompost and conventional aerobic compost produced from municipal organic solid waste used in Amaranthus viridis production during the period from October 2014 to June 2015 at the Horticulture Research Centre of the Bangladesh Agriculture Research Institute, Gazipur, Bangladesh. In this study, three compost varieties (vermicompost, conventional aerobic compost, combination of vermicompost and conventional compost) and three levels of compost treatments (0, 100 and 150 g/m2) with three replications were applied. The plots were arranged in randomized complete block design. Vermicompost was prepared by using Eisenia fetida. Different composts (vermicompost and conventional aerobic compost) and plant sample were taken first for chemical and physical analysis to find out the effect of these composts on the growth of amaranth. The result of the study showed that different compost varieties significantly affected the chlorophyll content, dry matter content, height per plant, numbers of leaves, weight per plant, nitrogen, calcium, magnesium, potassium, total phosphorus positively in favour of vermicompost application and sulphur content, sodium, moisture content in conventional aerobic compost application. Vermicompost application showed higher result for growth and yield indices and nutrient content compared with conventional aerobic compost. J. Environ. Sci. & Natural Resources, 9(2): 43-49 2016